1995
DOI: 10.2337/diab.44.12.1447
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of β-Cell Dysfunction in the Male Zucker Diabetic Fatty Rat

Abstract: The molecular basis for the beta-cell dysfunction that characterizes non-insulin-dependent diabetes mellitus (NIDDM) is unknown. The Zucker diabetic fatty (ZDF) male rat is a rodent model of NIDDM with a predictable progression from the prediabetic to the diabetic state. We are using this model to study beta-cell function during the development of diabetes with the goal of identifying genes that play a key role in regulating insulin secretion and, thus, may be potential targets for therapeutic intervention aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(149 citation statements)
references
References 29 publications
7
142
0
Order By: Relevance
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 51%
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 51%
“…The toxic effect of hyperglycemia on ␤-cells has been demonstrated with in vivo (2)(3)(4)(5) and in vitro models (6, 7). Previously we found that hyperglycemia induces the expression of c-Myc in islets in several different diabetic models (5,13).…”
Section: Discussionmentioning
confidence: 99%
“…Once hyperglycemia becomes apparent, ␤-cell function deteriorates (1). The adverse effects of chronic hyperglycemia on ␤-cells, called glucose toxicity, have been demonstrated by various in vivo (2)(3)(4)(5) and in vitro studies (6,7). After chronic exposure to hyperglycemia, insulin gene transcription and glucose-stimulated insulin secretion are suppressed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic hyperglycaemia induces phenotypic alterations of rodent beta cells, including GSIS abnormalities, reduced expression of specific genes (loss of beta cell differentiation), hypertrophy, slight increase in apoptosis, and increased expression of genes normally repressed in fully differentiated beta cells [6,[8][9][10][11][12][13][14]. These phenotypic alterations may contribute to the progressive worsening of GSIS in type 2 diabetes [15,16].…”
Section: Introductionmentioning
confidence: 99%